Tinjauan Hukum Islam Tentang Praktek Tengkulak Dalam Jual Beli Karet Mentah - Deka Meuthia Novari (LPPM Institut Al-Ma'arif Way Kanan, 2020)
he problem that becomes the study of this research is how the practices of middlemen in determining the price of raw rubber and how is the view of Islamic law about the practice of middlemen in determining the price of raw rubber. The purpose of this study is to find out how the practice of middlemen in determining the price of raw rubber and to analyze how the views of Islamic law about the practice of middlemen in determining the price of raw rubber in Desa Riang, Blambangan Umpu District, Way Kanan Regency. The method used in this research is field research with qualitative descriptive research. The sample in this study is 26 farmers and 6 tengkula from the existing population and data collection techniques using interview, observation, and documentation methods. While to analyze The data is used deductive data processing method by using inductive thinking approach. The findings of this study are that rubber farmers in Desa Riang Village have a rubber price determination with quality. If the good quality and low quality have the same pricing and the rubber sales transaction uses a system of selling rubber with a free system carried out by rubber farmers who are not bound to one of the bosses or collectors in the village. Usually the person selling freely is someone who is capable enough to control his rubber products and is able to meet his daily needs and sell with a system bound to collectors, selling goods or rubber products from his garden in a bound because he has already been in debt for food ingredients and necessities other life. Thus he must pay it off by having to sell the results of tapping rubber to collectors. Based on the results of this study it can be concluded that the practice of middlemen in determining the price of raw rubber based on agreement with other middlemen without any agreement with the seller. This is detrimental to farmers because they have to follow the middlemen's agreement regarding the price of raw rubber, even though the price set by the middlemen is far from the market price. The practices carried out by middlemen are not in line with Islamic principles where fellow believers should help one another in the good and not harm each other.